Anne of Green Gables - Montgomery, L. M. (Lucy Maud), 1874-1942. (New York : Aladdin Paperbacks, 2001)
Anne, an eleven-year-old orphan, is sent by mistake to live with a lonely, middle-aged brother and sister on a Prince Edward Island farm and proceeds to make an indelible impression on everyone around her.
"Includes reading group guide"--Cover.
Keywords: Orphans -- Fiction; Friendship -- Fiction; Islands -- Fiction; Country life -- Prince Edward Island -- Fiction; Prince Edward Island -- History -- 20th century -- Fiction; Canada -- History -- 1867-1914 -- Fiction